A nanounit strategy reverses immune suppression of exosomal PD-L1 and is associated with enhanced ferroptosis - Guohao Wang (Nature Portfolio, 2021)
PD-L1 is frequently expressed on the surface of cancer cells and can be excreted from cancer cells in exosomes. Here, the authors generate a nanotherapy that combines an inhibitor of exosome production and an inducer of ferroptosis, enhancing the response to immune checkpoint blockade therapy.